MDSCs are involved in the protumorigenic potentials of GM-CSF in colitis-associated cancer. (June 2017) - Ma, Ning; Liu, Qilin; Hou, Lin; Wang, Yalin; Liu, Ziling
Chronic inflammation is thought to be a major driving force for the development of colitis-associated colorectal cancer (CAC). As one member of proinflammatory cytokine family, granulocyte macrophage colony-stimulating factor (GM-CSF) has been identified to play a key role in CAC pathogenesis recently. The underlying mechanisms, however, remain largely unknown. In this study, we found that myeloid-derived suppressor cells (MDSCs) accumulated increasingly in the lesions during the progression from colitis to cancer, which was critical for CAC formation. Importantly, this MDSC accumulation was controlled by GM-CSF. MDSC number decreased significantly in GM-CSF-deficient mice suffering from CAC induction, and transfusion of MDSCs from wild-type CAC-bearing mice into GM-CSF-deficient counterparts led to recurrence of CAC. Furthermore, the supernatants of CAC lesions or GM-CSF alone was sufficient to differentiate hematopoietic precursors into MDSCs. Addition of neutralizing anti-GM-CSF antibody impaired the MDSC-differentiating effects of the supernatants of CAC lesions. Overall, these findings shed new insights into the mechanisms of GM-CSF underlying CAC development, by inducing/recruiting CAC-promoting MDSCs. Blocking GM-CSF activity or MDSC function may represent new therapeutic strategies for CAC in clinic.